The relationship between motivation and pragmatic awareness: a case study of Chinese EFL learners - Rui Li,; Rozina Raja,; Azimah Sazalie, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
Motivation is assumed to play a crucial role in the acquisition of L2 pragmatics because it determines learners’ level of attention to the pragmatic information to be acquired, leading to more noticing or awareness of the target language features, and this awareness is necessary for converting input into intake (Kasper and Schmidt 1996, Schmidt 1993). This study investigated the relationship between motivation and pragmatic awareness among Chinese learners of English as a foreign language (EFL). The research data were collected from eighty-five Chinese university undergraduates majoring in English who were asked to complete a motivation questionnaire and a multiple-choice discourse completion test. Semi-structured interviews on learners’ judgment of language appropriateness and their English learning activities outside class were also conducted. Findings revealed Chinese EFL learners’ low level of pragmatic awareness and their difficulty in identifying the pragmatic force that different strategies and linguistic forms convey in English. Motivation was found to be significantly correlated with pragmatic awareness, and intrinsic interest was the most important contributor among the motivation subscales investigated. Compared with less motivated learners, relatively highly motivated learners were more concerned with the authentic L2 use and L2 culture when carrying out learning activities outside class, and they exerted more effort to enhance the opportunities to use the target language. These findings suggest that within the context of foreign/second language acquisition, motivation should be given greater emphasis and learners’ attention to authentic L2 use and L2 culture needs to be stimulated in the process of enhancing learners’ pragmatic awareness.